Kombinasi Nanopartikel Cisplatin-Withaferin Berbasis PEGylated Liposome Sebagai Terapi Alternatif Kanker Ovarium - Made VW Yani; Ida Ayu W Anjani; I Gede S Narayana; Desak M Wihandani; I Gede P Supadmanaba (Journal of Medicine and Health, 2020)
Ovarian cancer is one of the major health problems in gynecology worldwide. Globocan 2012 data shows that ovarian cancer occurs in 239.000 cases, and is placed fourth as the most malignancy occurred in Indonesia. So far, cisplatin is the most effective therapeutic agent, but the high dosage of administration often caused side effects. A new alternative therapy to overcome the problems by using withaferin-A and nanoparticle PEGylated liposome. WFA has the potential effect to reduce cisplatin resistance but has low bioavailability thus, it needs to be encapsulated. This review’s goal is to depict the potency of withaferin-A, cisplatin, and PEGylated liposome combination as a therapeutic agent to treat ovarian cancer. The combination of Cisplatin-Withaferin PEGylated Liposome is constructed by the modified thin lipid film hydration method then administered orally. This combination suppresses 70-80% of the ovarian cancer cell growth in vivo and inhibits NGFR from binding to TRKA, prevents cell migration as much as 50%. Nano-Cisferin-Liposome, inhibits migration of ovarian cancer cell significantly through ?-catenin signaling through ALDH1 that disturb the spheroid formation, and increase apoptosis event as much 70-80% by increasing ROS production up to 2,5 times. Thus, Nano-Cisferin-Liposome (NCL) has potential as a therapeutic agent for treating ovarian cancer. Keywords: Cisplatin; Ovarian Cancer; PEGylated Liposome; Withaferin A